Bisoprolol compared with carvedilol and metoprolol succinate in the treatment of patients with chronic heart failure - Fröhlich, Hanna; Torres, Lorella; Täger, Tobias; Schellberg, Dieter; Corletto, Anna; Katus, Hugo; Frankenstein, Lutz (Clinical research in cardiology, 2017)
AimsBeta-blockers are recommended for the treatment of chronic heart failure (CHF). However, it is disputed whether beta-blockers exert a class effect or whether there are differences in efficacy between agents.Methods and results6010 out-patients with stable CHF and a reduced left ventricular ejection fraction prescribed either bisoprolol, carvedilol or metoprolol succinate were identified from three registries in Norway, England, and Germany. In three separate matching procedures, patients were individually matched with respect to both dose equivalents and the respective propensity scores for beta-blocker treatment. During a follow-up of 26,963 patient-years, 302 (29.5%), 637 (37.0%), and 1232 (37.7%) patients died amongst those prescribed bisoprolol, carvedilol, and metoprolol, respectively. In univariable analysis of the general sample, bisoprolol and carvedilol were both associated with lower mortality as compared with metoprolol succinate (HR 0.80, 95% CI 0.71-0.91, p < 0.01, and HR 0.86, 95% CI 0.78-0.94, p < 0.01, respectively). Patients prescribed bisoprolol or carvedilol had similar mortality (HR 0.94, 95% CI 0.82-1.08, p = 0.37). However, there was no significant association between beta-blocker choice and all-cause mortality in any of the matched samples (HR 0.90; 95% CI 0.76-1.06; p = 0.20; HR 1.10, 95% CI 0.93-1.31, p = 0.24; and HR 1.08, 95% CI 0.95-1.22, p = 0.26 for bisoprolol vs. carvedilol, bisoprolol vs. metoprolol succinate, and carvedilol vs. metoprolol succinate, respectively). Results were confirmed in a number of important subgroups.ConclusionOur results suggest that the three beta-blockers investigated have similar effects on mortality amongst patients with CHF.